(Un)beliveable wages? An analysis of minimum wage policies in Europe from a living wage perspective - Brian Fabo; Sharon Sarah Belli (IZA Journal of Labor Policy, 2017)
Minimum wage is one of the most debated issues in the labour policy area. Often perceived as a trade-off between employment and equality in earnings, the debate on minimum wage is highly polarized. With regard to the undergoing discussions on the Social Pillar of the European integration, we aim to extend the debate to include the aspect of minimum living standards, by empirically showing the gap between minimum wages and the minimum living wages in the peripheral countries of the European Union.
Keywords: J39; 330; Living wage; Minimum wage; EU Social Pillar